The Effect of Service Quality, Digital Promotion, Price, and Consumer Trust on Customer Loyalty at Tasya Bags Wholesale - Anita Amelia; Aulia Indra; Daslan Simanjuntak (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the influence of service quality, digital promotion, price, and consumer trust on customer loyalty at Tasya Bag Wholesale in Kampung Pajak. This study uses a quantitative approach with a survey method. The population in this study is all customers of Tas Tasya Wholesale, with sampling techniques using accidental sampling methods. Data were collected through questionnaire deployment and analyzed using multiple linear regression with the help of t-test, F-test, and coefficient of determination (R²). The results of the study show that partial service quality, digital promotion, price, and consumer trust have a positive and significant effect on customer loyalty. Simultaneously, these four variables also have a significant effect on customer loyalty. The consumer trust variable has the most dominant influence in increasing customer loyalty. The value of the determination coefficient indicates that customer loyalty can be explained substantially by the quality of service, digital promotions, price, and consumer trust, while the rest is influenced by other factors outside of the study. This study concludes that improving service quality, optimizing digital promotions, setting competitive prices, and building consumer trust are effective strategies to increase customer loyalty in Wholesale Tasya Bags in Tax Villages.